Enfermedades que afectan al cultivo de pitahaya (Selenicereus undatus). - Peña Aguiar, Anthony Sergio (2022)
This document dealt with the diseases that affect the cultivation of pitahaya (Selenicereus undatus). Pest prevention and control are highly relevant for the proper development of crops. The correct application of the techniques will make it possible to easily avoid the appearance of pests that may be harmful or detrimental to production. The conclusions determine that pitahaya is a low-calorie fruit, where its vitamin C content stands out. In addition, thanks to the presence of betalains, it is considered a promising natural food coloring; since its coloring power is comparable to synthetic dyes. Other of its benefits is its antioxidant power, which favors the generation of collagen, which slows down aging; The diseases Stem rot (Erwinia carotovora) and Fish eye (Dothiorella sp.) are the diseases that cause greater damage to the pitahaya crop and to control the diseases, synthetic fungicides such as propiconazole or prochloraz are used, in order to reduce economic losses and increase yields.